A Study on the Informal Economy Size of Emerging Southeast Asian Nations - Quang Trung Ngo (International Journal of Advanced Science and Technology, 2020)
In many countries, the size of the informal business sector including small-scaled stores, street vendors, private tailor shops, self-employed craftsmen, or scrap collectors, etc. even dominates the economy compared to the formal one. However, informal businesses are usually not easy to be managed and fairly assessed by the government. This could lead to an issue for the government in terms of developing, exploiting, and regulating the informal sector. Recognizing the significance of the informal economy, this paper aims to examine the size of the informal economies of some emerging countries in the Southeast Asian region, namely Indonesia, Malaysia, Philippines, Thailand, and Vietnam. By the quantitative method using the FEM analysis, this paper finds that the existence of informal economies in these countries is not small and there are large disparities between countries. In which, Thailand exists the largest informal economy size, while Vietnam is the smallest one. Additionally, the study identifies that the tax burden is the main factor leading to the informal economy among other variables, namely money supply, tax, saving interest rate, personal consumption, and GDP per capita. In general, the study aid policy-makers in Southeast Asian countries to have a better understanding of the factors leading to the informal economy, thereby they can effectively manage the economy. In many countries, the size of the informal business sector including small-scaled stores, street vendors, private tailor shops, self-employed craftsmen, or scrap collectors, etc. even dominates the economy compared to the formal one. However, informal businesses are usually not easy to be managed and fairly assessed by the government. This could lead to an issue for the government in terms of developing, exploiting, and regulating the informal sector. Recognizing the significance of the informal economy, this paper aims to examine the size of the informal economies of some emerging countries in the Southeast Asian region, namely Indonesia, Malaysia, Philippines, Thailand, and Vietnam. By the quantitative method using the FEM analysis, this paper finds that the existence of informal economies in these countries is not small and there are large disparities between countries. In which, Thailand exists the largest informal economy size, while Vietnam is the smallest one. Additionally, the study identifies that the tax burden is the main factor leading to the informal economy among other variables, namely money supply, tax, saving interest rate, personal consumption, and GDP per capita. In general, the study aid policy-makers in Southeast Asian countries to have a better understanding of the factors leading to the informal economy, thereby they can effectively manage the economy.